Evaluation of mechanical properties in carbon/epoxy composites with different curing parameters - F. Fonseca, Mariana H.; S. Lobo, Cândido J.; N. A. Lima, Arthur V.; N. Cavalcante, Fabrício J.; Cardoso , Jorge L.; Vilar , Zoroastro T. (Revista Colombiana de Materiales, 2020)
The intense research on the parameters involved in the composite materials grows every day due to the use of these materials in areas such as automotive, military and aeronautics. The use of composite materials is due to the possibility of combining desirable properties with the joining of metals, ceramics and/or polymers. The aim of this work was to evaluate the different conditions of improvement of the fabrication and curing process of the carbon fiber composite and epoxy resin, verifying if the differences are significant with the variations of resin volumetric fraction and curing process. For this purpose, the curing occurred due to the action of the vacuum, with the aid of the hydraulic press at a pressure of 1tnf with no pressure, all for 5 hours. For each type of curing process, the volumetric fraction of the resin was varied in 15%, 25%, 35% and 45%. Then, mechanical tensile, flexural and DMA tests were carried out and the results showed that there is an influence of the curing processes on the performance of the composites. The increase of the volumetric fraction of resin with hydraulic press and with no pressure showed a tendency of increase in the properties of tensile and flexural, respectively. In addition, for the vacuum process, it showed a better thermal stability. With this, depending on the application, one can choose the most suitable curing process.